Correction: A Cytosine Methytransferase Modulates the Cell Envelope Stress Response in the Cholera Pathogen. - Michael C Chao; Shijia Zhu; Satoshi Kimura; Brigid M Davis; Eric E Schadt; Gang Fang; Matthew K Waldor (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1005666.].